Jesus in the Himalayas - Salz, Jeff 1953; Adams, Bini; Cross, Ian; Tiballs, David (Discovery Travel & Adventure Channel, 2002)
This documentary investigates a popular legend of the Indian subcontinent, namely that Jesus spent part of his life traveling through the Himalayas. Anthropologist Jeff Salz retraces the journey allegedly made by Jesus, from the Indian foothills to the Tibetan border, following the principal trade routes of the biblical era.